2014
DOI: 10.1002/jctb.4486
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of degradation of winery‐derived biomass waste by Ascomycetes

Abstract: BACKGROUND: Recently, winery wastes have been classified as pollutants by the European Union and post-product processing is required to lower their hazards. Individual fungal enzymes have limited capacity so mixed fungal degradation combined with pre-treatment can decrease biomass recalcitrance for more efficient breakdown, overcoming these limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
(63 reference statements)
1
26
0
Order By: Relevance
“…A considerable increase of 2‐ketovaline indicated its possible use to produce biofuel molecules such as iso‐butanol by the post‐fermentation application of 2‐keto‐acid decarboxylases after eliminating acetolactate group enzymes . In addition, it has been observed that a pre‐treatment prior to SSF and a mixed fungal degradation considerably increases the biomass degradation. A continuous batch fermentation of the degraded biomass in a simultaneous and/or sequential manner by Saccharomyces cerevisiae , Pichia stipitisi or E. coli has been shown to utilize the mixed pentoses and hexoses generated by A. niger enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable increase of 2‐ketovaline indicated its possible use to produce biofuel molecules such as iso‐butanol by the post‐fermentation application of 2‐keto‐acid decarboxylases after eliminating acetolactate group enzymes . In addition, it has been observed that a pre‐treatment prior to SSF and a mixed fungal degradation considerably increases the biomass degradation. A continuous batch fermentation of the degraded biomass in a simultaneous and/or sequential manner by Saccharomyces cerevisiae , Pichia stipitisi or E. coli has been shown to utilize the mixed pentoses and hexoses generated by A. niger enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Shiraz was obtained from the Australian Wine Research Institute (AWRI), Glen Osmond, South Australia, Australia. The general composition of Shiraz grape biomass consisted of proteins (2.2%), sugars (1.9%), lignin (35.9%), ash (2.8%) and cellulose–hemicellulose (57.8%) . Further details of the biochemical composition of untreated grape biomass are given in Table S1, Supplementary material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few of recent studies which were conducted to use fungi for degrading hemicellulose biomass from winery (Karpe et al, 2015a(Karpe et al, , 2015b. There is a need to develop a technology for conversion of winery wastes to value-added products, leading to sustainable waste management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has been applied to understand metal corrosion and metals in the environment (Beale et al, 2010;Jones et al, 2015), food contamination , general fungal and yeast metabolism (Brown et al, 2013;Christensen & Nielsen, 2000;Larsson, Snoep, Norbeck, & Albers, 2011;Niklas, Schneider, & Heinzle, 2010;Si, Luo, Xiao, & Zhao, 2014), and fungal based biomass degradation (Karpe, Beale, Harding, & Palombo, 2015). Furthermore, quantitative and qualitative metabolic profiling and flux analysis methods have been used to indicate the consumption of various substrates and relevant product generation.…”
Section: Mic Biofilm Metabolome and Metabolomicsmentioning
confidence: 99%